2018
DOI: 10.4022/jafib.2038
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of the Spectral Tissue Doppler E/e’ Ratio in the Management of Patients with Atrial Fibrillation: a Comprehensive Review of the Literature.

Abstract: Atrial fibrillation is the most common cardiac rhythm disorder observed in clinical practice. It carries high morbidity and mortality rates, primarily related to heart failure, stroke and death. Validation of noninvasive markers in the diagnosis of heart failure with preserved ejection fraction and risk stratification is relevant in this clinical setting. The spectral tissue Dopplerderived E/e' ratio is a simple and reproducible index, which has been validated in noninvasive assessment of left ventricular dias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Another important aspect of our case is the presence of significant LV diastolic dysfunction, that went unexplained and was wrongly attributed to hypertensive heart disease. The evaluation of diastolic dysfunction in Afib can be challenging ( 22 , 23 ). In our case unequivocal findings were present: firstly, dilation of the LA, that was the reason for the precocious Afib ( Figure 3 ) associated with an E/e' > 12 ( Figure 4 ) and secondarily, mild-moderate pulmonary hypertension (45 mmHg systolic) ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another important aspect of our case is the presence of significant LV diastolic dysfunction, that went unexplained and was wrongly attributed to hypertensive heart disease. The evaluation of diastolic dysfunction in Afib can be challenging ( 22 , 23 ). In our case unequivocal findings were present: firstly, dilation of the LA, that was the reason for the precocious Afib ( Figure 3 ) associated with an E/e' > 12 ( Figure 4 ) and secondarily, mild-moderate pulmonary hypertension (45 mmHg systolic) ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…These patients were referred for a comprehensive cardiovascular evaluation by their general practitioners thus reflecting a primary care setting. The clinical question was to assess whether the available evidence reported in multiple, different experimental settings [1][2][3][4][19][20][21] may be duplicated in the heterogeneous clinical scenario encountered in every day clinical practice. During a midterm follow-up, e' and E/e' were both associated with clinical outcome in these patients, but only e' maintained its independent prognostic information in multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that TDI indices of diastolic function provide information on outcome which is incremental to conventional 2D-DE in general population and multiple conditions [ [1][2][3][4]. Of particular interest, Kuznetsova et al [4], in 793 individuals from the general population (mean age 51 years), showed that e' velocity was a significant predictor of fatal and nonfatal cardiovascular and cardiac events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 A recent review has highlighted the usefulness of E/e' in the prediction of adverse outcome in patients with atrial fibrillation (heart failure, stroke, death, left atrial appendage thrombus, recurrence of arrhythmia). 6 Studies have reported the prognostic value of E/e' in the full spectrum of ischemic heart disease. [7][8][9] Other clinical studies have also offered evidence that E/e' predicts outcome in patients with hypertensive heart disease, hypertrophic cardiomyopathy, asymptomatic aortic stenosis, and even in critically ill patients.…”
mentioning
confidence: 99%